2009
DOI: 10.1016/j.jhazmat.2009.02.121
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the reactivity of metallic iron upon methylene blue discoloration in Fe0/MnO2/H2O systems

Abstract: A simple method is proposed for testing the reactivity of elemental iron materials (Fe 0 materials) using methylene blue (MB) as reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…3 and vary from 13 μg h -1 for ZVI8 to 37 μg h -1 for ZVI10. The least reactive material (ZVI8 from Würth) was used as negative reference like in previous studies [32][33][34]. The most reactive material were ZVI9 (Ferblast) and ZVI10 (Peerless).…”
Section: Edta Batch Test 421 All Tested Materialsmentioning
confidence: 99%
“…3 and vary from 13 μg h -1 for ZVI8 to 37 μg h -1 for ZVI10. The least reactive material (ZVI8 from Würth) was used as negative reference like in previous studies [32][33][34]. The most reactive material were ZVI9 (Ferblast) and ZVI10 (Peerless).…”
Section: Edta Batch Test 421 All Tested Materialsmentioning
confidence: 99%
“…The results of experiments using such different materials have been compared to each other with little care on the intrinsic material reactivity (see next section). To date there is no standard parameter to evaluate the intrinsic reactivity of Fe 0 materials [17]. However, it is well known that, the metal type and method of manufacture are as important as the environment (solution corrosiveness) for corrosion processes [18].…”
Section: Introductionmentioning
confidence: 99%
“…A tentative order of increasing reactivity based on these values is: ZVI3 < ZVI1 < ZVI2 < ZVI4. Note that the order of reactivity after the EDTA-test (Noubactep et al, 2005; and the MB-test (Noubactep, 2009) were univocally: ZVI2 < ZVI1 = ZVI3 = ZVI4. Accordingly, air-homogenised batch experiments are not appropriate for the differentiation of the reactivity of ZVI1, ZVI3 and ZVI4.…”
Section: Resultsmentioning
confidence: 99%
“…surface state). However, it has been traceably demonstrated that none of these structural and physical characteristics is really determinant for the chemical reactivity of Fe 0 (Reardon, 1995;Landis et al, 2001: Noubactep et al, 2005Reardon, 2005;Noubactep et al, 2009). For instance, Landis et al (2001) reported that Fe 0 materials of comparable particle size (comparable surface area) exhibited reactivity differences greater than 3-fold for cDCE and VC degradation rates in column studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation